2015
DOI: 10.1159/000442151
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa-Carbidopa Intestinal Gel Infusion Therapy in Advanced Parkinson's Disease: Single Middle Eastern Center Experience

Abstract: Background: Levodopa therapy in Parkinson's disease (PD) is often associated with disabling motor and non-motor complications in patients with advanced disease due to the variable absorption of levodopa because of an irregular or erratic emptying of the gastric content. Methods: Prospective single movement disorder center study using pre-set selection criteria, unified PD scale (UPDRS III), non-motor symptoms scale (NMSS), and PD questionnaire-8 (PDQ-8) to evaluate the efficacy, safety, and long-term treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…Similar improvements of NMSs and QoL were demonstrated in two other open‐label studies with smaller patient collectives over a 12‐month and a mean 48‐month follow‐up period .…”
Section: Discussionsupporting
confidence: 78%
“…Similar improvements of NMSs and QoL were demonstrated in two other open‐label studies with smaller patient collectives over a 12‐month and a mean 48‐month follow‐up period .…”
Section: Discussionsupporting
confidence: 78%
“…It could be interesting to investigate the acute effect on NMS of levodopa-carbidopa intestinal gel (LCIG) among LSPD patients. In fact, some recent reports suggest an improvement of some NMS such as sleep/fatigue, pain, gastrointestinal and urinary symptoms , as assessed by the NMSS, during a chronic treatment with LCIG [31][32][33], the quality of evidence for reduction of NMS is still considered low [34] and no study have been specifically addressed to LSPD patients .…”
Section: Discussionmentioning
confidence: 99%
“…Previous long‐term LCIG safety and efficacy studies were limited by retrospective or registry study design and small data sets . Recently, larger randomized, controlled, and open‐label prospective studies demonstrated the safety and efficacy of LCIG treatment through 1 year, and safety was demonstrated for an average of 2 years in an open‐label extension study .…”
mentioning
confidence: 99%